2011
DOI: 10.1249/mss.0b013e318222edf3
|View full text |Cite
|
Sign up to set email alerts
|

Human Muscle Proteome Modifications after Acute or Repeated Eccentric Exercises

Abstract: These findings suggest that the eccentric training resulted in a switch to oxidative metabolism, which may be associated with protection from DOMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
61
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 25 publications
5
61
0
Order By: Relevance
“…It worth to notice that eccentric exercise induced increased muscular oxidative metabolism (increased UQCRC1 expression). Similar result of a switch to oxidative metabolism after eccentric exercise has also been observed in a recent study on human skeletal muscles analyzed with proteomics (Hody et al 2011). Interestingly, in a recent study on human skeletal muscle after exhaustive concentric contraction, using whole-genome screen to analyze muscle biopsies taken 30 min and 3 h after the exercise Crane et al (2012) have revealed up-regulation in many Z-band related proteins such as actin, alpha-actinin, obscurin and filamin compared to control muscles, similar to the present and our previous findings Carlsson et al 2008).…”
Section: Discussionsupporting
confidence: 87%
“…It worth to notice that eccentric exercise induced increased muscular oxidative metabolism (increased UQCRC1 expression). Similar result of a switch to oxidative metabolism after eccentric exercise has also been observed in a recent study on human skeletal muscles analyzed with proteomics (Hody et al 2011). Interestingly, in a recent study on human skeletal muscle after exhaustive concentric contraction, using whole-genome screen to analyze muscle biopsies taken 30 min and 3 h after the exercise Crane et al (2012) have revealed up-regulation in many Z-band related proteins such as actin, alpha-actinin, obscurin and filamin compared to control muscles, similar to the present and our previous findings Carlsson et al 2008).…”
Section: Discussionsupporting
confidence: 87%
“…The impairment in mitochondrial oxidative capacity is shown to play a fundamental role in early LVH, even before the onset of hypertension [76]. In contrast, alterations in mitochondrial enzymes induced by endurance exercise are associated with improvement in cardiovascular capacity [17,32,66,77,78] and are generally opposite to proteomic changes seen in heart failure induced by hypertension [79][80][81]. With the exception of polyubiquitin B and C, related to ubiquitin-proteosome-mediated muscle protein degradation [82], all metabolic proteins related with PCr, nucleotide, FAO, and glucose oxidation were enhanced (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise proteomics was used to study protein alterations in humans (Malm et al2012;Egan et al 2011;Norheim et al 2011;Hody et al 2011;Moriggi et al 2010;Holloway et al 2009) and animal models of physical activity Magherini et al 2012;Macedo et al 2012;Yamaguchi et al 2010;Bouwman et al 2010;Burniston 2008;Donoghue et al 2007;Guelfi et al 2006;Donoghue et al 2005). The neuromuscular system has a vast capacity to become accustomed to a great variety of physical demands and differing training conditions by muscle remodelling involving changes in contractile properties, metabolic pathways and tissue mass (Bassel and Olson 2006).…”
Section: Proteomics Of Endurance Exercisementioning
confidence: 99%
“…Besides the currently used serum biomarkers, creatine kinase and carbonic anhydrase, the application of proteomics promises to identify improved markers of rhabdomyolysis, as well as indicators of the natural secretion process that releases myokines and other fibre-associated indicators during exercise-induced adaptations. Proteomics has so far been applied to determine global changes in the case of delayedonset muscle soreness in response to acute or repeated eccentric exercises (Hody et al 2011) and skeletal muscle damage as a result of extensive downhill running in human athletes, as well as in an animal model of overtraining using an excessive treadmill endurance exercise ). Surprisingly, myosin heavy chains and glycolytic enzymes decreased after eccentric tests, suggesting that eccentric training may trigger a switch to oxidative metabolism to protect against delayed-onset muscle soreness (Hody et al 2011).…”
Section: Proteomics Of Overtraining and Muscular Injurymentioning
confidence: 99%
See 1 more Smart Citation